Design and implementation of a system to determine property tax through the processing and analysis of satellite images (2020)
One of the main objectives when implementing metaheuristics in engineering problems, is to solve complex situations and look for feasible solutions within a defined interval by the design dimensions. With the support of heuristic techniques such as neural networks, it was possible to find the sections that allow to obtain the characteristics of interest to carry out the study of the important regions of an image. The analysis and digital processing of images allows to smooth the file and to section the area of analysis in regions defined as rows and columns, results in a matrix of pixels, this way carrying out the measurement of the coordinates of the beginning and end of the region under analysis, taking it as a starting point for the creation of a frame of references to be examined. Once this requirement is completed, it is possible to return to the smoothed image with which the high edges of the image will be determined by means of the Gaussian function, thus finding the edges generated for the structures of interest.